2004
DOI: 10.1017/s095026880400233x
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 subtype in Scotland: the establishment of a national surveillance system

Abstract: Historically, subtype B viruses in men who have sex with men (MSM) and injecting drug users (IDU) dominated the HIV epidemic in the United Kingdom, whereas non-B heterosexual infections dominate globally. Heterosexual contact is now the most common route of transmission in the United Kingdom. Here we monitor HIV subtype in Scotland, and link it to origin of infection. HIV-1 sequence was generated from new diagnoses and the subtype thus obtained linked with demographic data. Virus was subtyped from 80% (137/171… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…[30][31][32] Also in France among the MSM with a new HIV-1 diagnosis the highest proportion of recent infections (46.0%) and an elevated percentage of non-B subtypes (12.0%), after 2003, have been observed. 19 Nevertheless, there are relatively few data on HIV-1 genetic diversity among MSM in Europe, and most of the available data have been provided by national surveillance systems 33,34 or from serosurveys of individuals attending HIV-1 screening programs in urban STI clinics. The overall percentage of non-B subtypes in our cohort (13.5%) is higher than the percentage reported in some northern European countries, which range from 4% to 12%, [17][18][19]34 although it is not even half of that observed in Greece.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] Also in France among the MSM with a new HIV-1 diagnosis the highest proportion of recent infections (46.0%) and an elevated percentage of non-B subtypes (12.0%), after 2003, have been observed. 19 Nevertheless, there are relatively few data on HIV-1 genetic diversity among MSM in Europe, and most of the available data have been provided by national surveillance systems 33,34 or from serosurveys of individuals attending HIV-1 screening programs in urban STI clinics. The overall percentage of non-B subtypes in our cohort (13.5%) is higher than the percentage reported in some northern European countries, which range from 4% to 12%, [17][18][19]34 although it is not even half of that observed in Greece.…”
Section: Discussionmentioning
confidence: 99%
“…19 Nevertheless, there are relatively few data on HIV-1 genetic diversity among MSM in Europe, and most of the available data have been provided by national surveillance systems 33,34 or from serosurveys of individuals attending HIV-1 screening programs in urban STI clinics. The overall percentage of non-B subtypes in our cohort (13.5%) is higher than the percentage reported in some northern European countries, which range from 4% to 12%, [17][18][19]34 although it is not even half of that observed in Greece. 5 The percentage of non-B infections in our study is higher than that found in previous studies conducted in Italy among MSM, heterosexual contacts, and IDUs, 13,[36][37][38][39] yet it is similar to that of another study, 40 reflecting the increasing circulation of non-B subytpes in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…As ARVs are becoming more readily available throughout the world this imbalance must be addressed such that there is sufficient knowledge accrued to decide whether all subtypes can be considered equal in terms of response to treatment and in development and transmission of drug resistance. Furthermore, in Europe infections with non-B subtypes are being detected with increasing frequency 5 (Gifford et al, submitted), making knowledge of subtype differences pertinent to both the developed and developing world.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we analysed Envs from infections acquired in six African countries and from Scotland, UK. Our replicationcompetent viruses with new Envs represent a diverse range of contemporary subtype C isolates for which we have determined coreceptor usage and sensitivity to neutralizing antibodies.Plasma samples were obtained from 13 HIV-1 subtype C infected, treatment naive individuals diagnosed in Scotland through the National Surveillance System (Yirrell et al, 2004). The undisclosed patients' origins and viral loads are presented in Supplementary Table S1 (available in JGV Online).…”
mentioning
confidence: 99%
“…Plasma samples were obtained from 13 HIV-1 subtype C infected, treatment naive individuals diagnosed in Scotland through the National Surveillance System (Yirrell et al, 2004). The undisclosed patients' origins and viral loads are presented in Supplementary Table S1 (available in JGV Online).…”
mentioning
confidence: 99%